Fat spouses and hours of work: are body and Pareto weights correlated? - Oreffice, S; Quintana-Domeque, C (Springer Open, 2012)
We explore the relationship between relative physical attractiveness in the household and the hours worked by married men and women. Using PSID data, we find that husbands who are thinner relative to their wives work fewer hours, while wives who are heavier relative to their husbands work more hours. These results are robust to controlling for individual, spousal characteristics, and conventional distribution factors, suggesting that highbodyweight leads to lowParetoweight in the household: fatter spouses may compensate with more hours of work. Our household bargaining interpretation is supported by the fact that we cannot statistically reject the collective proportionality restriction when including measures of the distribution of relative physical attractiveness in the population.